2019
DOI: 10.4103/ams.ams_67_19
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial injuries in motorcyclists following the implementation of helmet

Abstract: Background:It has been reported that 20%–60% of all people injured in road traffic accidents (RTAs) tend to have some form of maxillofacial injury. Mangalore city, Karnataka State, India, traffic police has enforced the law to wear helmets to tackle the problem. The outcome of the initiative till date was not measured. Therefore, the objective of the study was to assess the prevalence of maxillofacial injuries among the victims of motorized two-wheeler RTAs, following the passing of the helmet law.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Children and older individuals are less frequently affected. Several studies 4,5 reported similar findings.…”
Section: Table-1: Age Distribution Of the Patients (N=30) Age Group (...supporting
confidence: 58%
“…Children and older individuals are less frequently affected. Several studies 4,5 reported similar findings.…”
Section: Table-1: Age Distribution Of the Patients (N=30) Age Group (...supporting
confidence: 58%
“…Enacting and enforcing stricter laws mandating helmet use has been shown to reduce the incidence of maxillofacial trauma among crashes and further reduce the proportion that result in facial fractures. [18][19][20] Alternatively, relaxing such laws saw a decrease in helmet use resulting in an increased incidence of head trauma and related trauma. 21 When a patient presents following an assault, a facial fracture should be an immediate concern.…”
Section: Discussionmentioning
confidence: 99%